Interprofessional collaboration between health teams of emergency services: integrative review (Research, Society and Development, 2020)
Objective: To identify the evidence available in the literature on the process of interprofessional collaboration between health teams of emergency services. Methodology: integrative review. The search for primary studies was performed in four relevant health databases, with a sample of 22 studies. Results: The synthesis of the primary articles originated two categories: a) Interprofessional collaboration: specific and shared attributions of professionals working in emergency services teams b) Facilitators and barriers to collaborative practical implementation in emergency services. Private and shared attributions of professionals working in emergency and emergency services, as well as intervening factors in interprofessional collaboration, such as: communication, physical structure, human resources and materials and professional experience were evidenced. Conclusion: interprofessional articulation is not easy to reach, because the professions are still very rooted in the knowledge of their field and with difficulties in promoting articulation.